Pembuatan Cokelat Berinti Wajik dengan konsentrasi Sirup Glukosa Berbeda di Dalam Inti - Shanti Fitriani; Mamot Said (Universitas Riau, 2007)
In this study, wajik formulation containing different percentages of glucose syrup were developed and their suitabilities as chocolate filling were studied. Then the products were studied for their qualities for two weeks using thermal cycle method. Data obtained were treated by the analysis of variance followed by Duncan New’s Multiple Range Test. The chocolates containing wajik with different percentage of glucose syrup show that there was no significant difference based on hardness, water activity, and color during storage. There were no fat bloom formed during the storage of chocolate. Result from sensory evaluation show that the chocolate containing wajik with 20% glucose syrup was more acceptable than that with 10% glucose syrup.